PENGARUH WAKTU PENUNDAAN PADA PEMERIKSAAN KIMIA URIN METODE CARIK CELUP DENGAN SUHU PENYIMPANAN 2-8oC - Meildy E. Pascoal; Febbyola A. C. Samaili; Allan J. Andaria; Sabrina Prisscilya Magdalena Pinontoan (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Changes in urine composition may occur in a specimen that allowed to remain unpreserved at room temperature for longer than 2 hours, without preservatives. Urine received in the laboratory often cannot be directly examined because the number of samples is not comparable to laboratory facilities or because urine collection is carried out at the patient's home or doctor's practice. So that urine is often delayed examination time. This study aims to determine the effect of the delay in urine samples stored at a temperature of 2-8oC on the results of urine chemistry examination using the strip-dip method. This type of research is a quasi-experimental research type. The samples used were 50 respondents who were determined by Quota sampling which were then examined for urine chemistry immediately, a delay of 1 hour, 2 hours, and 3 hours at a storage temperature of 2-8oC. Data analysis using Kruskal Wallis test.The results found there was an effect of delay time on urine chemistry examination using the stripping method on the results of leukocyte examination with a significant level value of 0.001 which means (p <0.05) and no effect on the results of the examination of nitrite, urobilinogen, protein, pH, blood, specific gravity, ketones, bilirubin and glucose.